PENGEMBANGAN MODEL EDUKASI BERBASIS VIDEO SINEMATOGRAFI DALAM MENINGKATKAN FAMILY SUPPORT PADA LANSIA DI MELINGGIH, PAYANGAN, BALI - Ni Luh Putu Inca Buntari Agustini; Ida Ayu Ningrat Pangruating Diyu; Ni Putu Ayu Ratna Dewi; Dewa Gede Wisnu Wardana; I Made Dwi Krisma Prataba; Ni Luh Gede Hari Nugrahini (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2023)
The family is one of the coping mechanisms that the elderly have as they live out their old age. One of the efforts to increase family support as care providers for the elderly is education. The service activities carried out by the ITEKES Bali Master of Nursing program aim to develop a cinematographic video-based educational model for increasing family support. The activity was carried out in October 2022 with 31 elderly people. The activity began with a pretest and continued with a posttest 5 days after the activity ended to find out whether there was a change in family support received by the elderly before and after giving the cinematography video using the family support system questionnaire. The analytical test used is the Wilcoxon test. The results showed that there was an effect of providing cinematographic videos on family support with a p value <0.001. This shows that family support after being given cinematographic videos has increased from low-to-moderate to high. It is hoped that the development of cinematographic video-based education can be applied to providing counseling to family members regarding the importance of family support.